Impulse Buying on Social Commerce Platforms Applying the Sor Framework to Tiktok Live Shopping in Indonesia - Edinur Ilham; Jaya Dwi Nurcholis (Jurnal Informatika Ekonomi Bisnis, 2026)
This research investigates consumer impulse buying behavior on TikTok's live shopping feature in Indonesia using the Stimulus-Organism-Response framework. Based on 237 questionnaires from new users, the study employed the SEM-PLS method for analysis. The results indicate that stimuli such as attractiveness and trustworthiness positively influence perceived enjoyment. Meanwhile, purchase convenience, product information, and price positively affect perceived usefulness. Both of these factors perceived enjoyment and usefulness were found to significantly increase the urge to buy impulsively (the response). In conclusion, consumers on live shopping platforms are more prone to making impulse purchases due to the direct encouragement and interaction provided by hosts during the broadcast.